Proceedings of the 16th International Conference on Multimodal Interaction 2014
DOI: 10.1145/2663204.2666276
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Autocorrelation in Real World Emotion Recognition

Abstract: Multimodal emotion recognition in real world environments is still a challenging task of affective computing research. Recognizing the affective or physiological state of an individual is difficult for humans as well as for computer systems, and thus finding suitable discriminative features is the most promising approach in multimodal emotion recognition. In the literature numerous features have been developed or adapted from related signal processing tasks. But still, classifying emotional states in real worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Nevertheless, in this paper we focus on methodologies that are based on neural networks since they achieved the best performance. The interested reader may refer to [14,3,61,33,9,60,71,40,84] for further details.…”
Section: Deep Learning Methodologies For Facial Expression Recognitiomentioning
confidence: 99%
“…Nevertheless, in this paper we focus on methodologies that are based on neural networks since they achieved the best performance. The interested reader may refer to [14,3,61,33,9,60,71,40,84] for further details.…”
Section: Deep Learning Methodologies For Facial Expression Recognitiomentioning
confidence: 99%
“…An interesting future line of research is to experiment with novel sensing technologies to capture behavioral data (physiological data, facial expressions, speech, ...) in order to detect emotions and to adapt recommendations based on emotional responses. Although measurement of emotions in a controlled laboratory environment is well studied for years by a large number of research groups [20], multimodal emotion recognition in real world environments is still a challenging task [17]. A good review of existing methods has been reported by Hrabal [13].…”
Section: Adaptivementioning
confidence: 99%